Effects of potassium fertilization on initial growth of Khaya senegalensis A. Juss in the Cerrado biome - Araújo, Matheus da Silva; D’Abadia, Karolayne Lemes; Cunha, Stephany Diolino; Coelho, Gustavo Matos; Morais, Yago Cesar Rodrigues; Barretto, Vitor Corrêa de Mattos; Calixto Junior, José Eduardo Dias (Revista Ecologia e Nutrição Florestal - ENFLO, 2018)
In the present study, it was aimed to evaluate the initial growth of seedlings of African mahogany (Khaya senegalensis A. Juss.) composted with different doses of potassium. The experiment was conducted in a greenhouse, in plastic container with capacity for 7 dm³ and using soil as substrate classified as red-yellow Oxisols. The experimental design was completely randomized, with five treatments and five replications, totaling 25 experimental units. The treatments had consisted of five doses of K: 0; 40; 80; 120 and 160 mg dm-³, using the application of potassium chloride. To 150 days, were measured the height of the plant, the diameter of the collect and the mass of dry matter of leaf, stem, root and total dry matter mass. It was found that increasing potassium doses promoted increase in plant growth. The African mahogany presented low potassium requirement in the early stages of development for the edafoclimatic condition on the site of the experiment.